Nerve Root Sparing En Bloc Resection of Sacral Chondrosarcoma: Technical Note and Review of the Literature. Issue 6 (15th November 2021) - Pairojboriboon, Sutipat; Sacino, Amanda; Pennington, Zach; Lubelski, Daniel; Yang, Robin; Morris, Carol D; Suk, Ian; Sciubba, Daniel M; Lo, Sheng-fu Larry
Abstract: BACKGROUND: Total en bloc sacrectomy provides the best long-term local control for large primary bony sacral tumors, but often requires lumbosacral nerve root sacrifice leading to loss of ambulation and/or bowel, bladder, and/or sexual dysfunction. Nerve-sparing techniques may be an option for some patients that avoid these outcomes and accordingly improve postoperative quality of life. OBJECTIVE: To describe the technique for a posterior-only en bloc hemisacrectomy with maximal nerve root preservation and to summarize the available literature. METHODS: A 38-yr-old woman with a 7.7 × 5.4 × 4.5 cm biopsy-proven grade 2 chondrosarcoma involving the left L5-S2 posterior elements underwent a posterior-only left hemisacrectomy tri-rod L3-pelvis fusion. A systematic review of the English literature was also conducted to identify other descriptions of high sacrectomy with distal sacral nerve root preservation. RESULTS: Computer-aided navigation facilitated an extracapsular resection that allowed preservation of the left-sided L5 and S3-Co roots. Negative margins were achieved and postoperatively the patient retained ambulation and good bowel/bladder function. Imaging at 9-mo follow-up showed no evidence of recurrence. The systematic review identified 4 prior publications describing 6 total patients who underwent nerve-sparing sacral resection. Enneking-appropriate resection was only obtained in 1 case though. CONCLUSION: Here we describe a technique for distal sacral nerve root preservation during en bloc hemisacrectomy for a primary sacral tumor. Few prior descriptions exist, and the present technique may help to reduce the neurological morbidity of sacral tumor surgery.